Acrylamide exposure increases cardiovascular risk of general adult population probably by inducing oxidative stress, inflammation, and TGF-β1: A prospective cohort study. (June 2022) - Wang, Bin; Wang, Xing; Yu, Linling; Liu, Wei; Song, Jiahao; Fan, Lieyang; Zhou, Min; Yang, Meng; Ma, Jixuan; Cheng, Man; Qiu, Weihong; Liang, Ruyi; et al.
Graphical abstract: Highlights: Acrylamide (ACR) exposure was associated with increased cardiovascular (CV) risk. Long-term daily ACR exposure could longitudinally increase CV risk over 3 years. ACR exposure was related to oxidative stress, inflammation, and TGF-β1 induction. Oxidative stress, inflammation, and TGF-β1 mediated ACR-associated CV risk increase. Abstract: Acrylamide (ACR) exposure and consequent health hazards are alarming public health issues that attract worldwide concern. The World Health Organization urges more researches into health hazards from ACR exposure. However, whether and how ACR exposure increases cardiovascular risk remain unclear, and we sought to address these issues in this prospective cohort study conducted on 3024 general adults with 3-year follow-up (N = 871 at follow-up). Individual urinary ACR metabolites (N-Acetyl-S-(2-carbamoylethyl)-L-cysteine [AAMA] and N-Acetyl-S-(2-carbamoyl-2-hydroxyethyl)-L-cysteine [GAMA]) as credible biomarkers of ACR exposure were detected to assess their cross-sectional and longitudinal relationships with 10-year cardiovascular disease (CVD) risk, a well measure of overall cardiovascular risk. Besides, biomarkers of oxidative stress (urinary 8-hydroxy-deoxyguanosine [8-OHdG] and 8-iso-prostaglandin-F2α [8-iso-PGF2α]) and inflammation (circulating mean platelet volume [MPV] and plasma C-reactive protein [CRP]) as well as plasma transforming growth factor-β1 (TGF-β1) were measured to assess their mediating/mechanistic roles in the relationships of ACR metabolites with 10-year CVD risk. We found AAMA, GAMA, and ΣUAAM (AAMA + GAMA) were cross-sectionally and longitudinally related to increased 10-year CVD risk with odds ratios (95% confidence intervals [CIs]) of 1.32 (1.04, 1.70), 1.81 (1.36, 2.40), and 1.40 (1.07, 1.82), respectively, and risk ratios (95% CIs) of 1.99 (1.10, 3.60), 2.48 (1.27, 4.86), and 2.13 (1.15, 3.94), respectively. Furthermore, 8-OHdG, 8-iso-PGF2α, MPV, CRP, and TGF-β1 were found to significantly mediate 8.06–48.92% of the ACR metabolites-associated 10-year CVD risk increment. In summary, daily ACR exposure of general adults was cross-sectionally and longitudinally associated with increased cardiovascular risk, which was partly mediated by oxidative stress, inflammation, and TGF-β1, suggesting for the first time that ACR exposure may well increase cardiovascular risk of general adult population partly by mechanisms of inducing oxidative stress, inflammation, and TGF-β1. Our findings have important public health implications that provide potent epidemiological evidence and vital mechanistic insight into cardiovascular risk increment from ACR exposure.